2014
DOI: 10.5665/sleep.3394
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Obstructive Sleep Apnea Severity in Adenotonsillectomy Candidates

Abstract: Clinicaltrials.gov (#NCT00560859).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
103
3
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 138 publications
(116 citation statements)
references
References 37 publications
8
103
3
2
Order By: Relevance
“…Further risk factors are African American race and environmental tobacco smoke, which show significant associations with the apnea-hypopnea index in children [12].…”
Section: Introductionmentioning
confidence: 99%
“…Further risk factors are African American race and environmental tobacco smoke, which show significant associations with the apnea-hypopnea index in children [12].…”
Section: Introductionmentioning
confidence: 99%
“…Volumetric measurements suggest that the adenoids and tonsils are significantly increased in children with OSA compared with matched control subjects, concomitant with smaller upper airway and larger soft palate volumes adding additional restriction to the airway lumen size (83,84). Therapy for OSA in children may involve surgery (e.g., adenotonsillectomy), positive pressure ventilation, oral appliances, and weight normalization if indicated.…”
Section: Pediatric Obstructive Sleep Apneamentioning
confidence: 99%
“…Prior research has demonstrated increased OSA prevalence 36 and lower CPAP adherence 13,37 in African Americans (AA). Our data demonstrate 15.0% of the study population to be AA, which is disparate from the 4.4% of the Colorado state census identified as AA in 2013 (quickfacts.census.gov).…”
Section: Inclusion Criteriamentioning
confidence: 99%